Megoura crassicauda promote the ability of Vicia faba L. to remediate cadmium pollution of water and soil - Sijing Wan; Shasha Wang; Yan Li; Yexin Xie; Qimei Li; Yinjie Fang; Zhenjuan Yin; Shigui Wang; Yifan Zhai; Bin Tang (Ecotoxicology and Environmental Safety)
With the increasing severity of heavy metal pollution in soil and water, phytoremediation is becoming increasingly popular because of its low cost, high returns, and environmental friendliness. The use of leguminous plants such as the broad bean for heavy metal remediation is becoming a research hotspot because of their symbiotic relationship with rhizobia. This study investigated the cadmium (Cd) remediation ability of fava beans by M. crassicauda feeding on or not using both hydroponic and soil cultures containing varying concentrations of Cd. Under hydroponic conditions, the Cd content in fava beans increased significantly following aphid invasion. while the Cd content decreased after aphid infestation under soil cultivation conditions. Aphid infestation significantly decreased the Cd content in both soil and hydroponic solution. However, there were no significant changes in germination rate and phenotype. We also found that prolonged Cd treatment increased the activities of stress-related antioxidant enzymes in fava beans, including superoxide dismutase, peroxidase, and malondialdehyde. After consumption by M. crassicauda, the levels of total sugar content underwent varying changes. These results demonstrate that fava beans not only exhibit high Cd tolerance but can also effectively absorb Cd ions from soil and water. Moreover, pest infestation can enhance broad bean remediation efficiency, making them potential targets for use in the phytoremediation of heavy metal pollution.